The ITSM Iron Triangle : Incidents, Changes and Problems. - McLean, Daniel (Stories in transforming ITIL® best practice into operational success, 1., 2012)
This innovative work of fiction demonstrates how ITIL® best practice can ensure the success of your IT process implementation projects. It is based on real-life, up-to-date situations and offers vital strategies to implement the most important aspects of ITIL into your business and to tailor them to your organization?s particular needs.